Activation of Protein C in Human Trophoblasts in Culture and Downregulation of Trophoblast Endothelial Protein C Receptor by TNF-α. (August 2015) - Faioni, E. M.; Fontana, G.; Razzari, C.; Avagliano, L.; Bulfamante, G.; Calvi, E.; Doi, P.; Marconi, A. M.
In mice, trophoblasts are equipped with a potent anticoagulant mechanism, the protein C pathway. In human placenta, no functional studies of the protein C pathway are available. Human first-trimester trophoblasts ( CK ++ HLA-G +/− Vim − ) were isolated and kept in culture for a maximum of 48 hours. Activation of protein C on trophoblasts was at least as efficient as in endothelial cells (4.43 × 10 − 7 nmol/L/min/cell). Endothelial protein C receptor (EPCR) was expressed in syncytiotrophoblasts and extravillous trophoblasts. Downregulation of the messenger RNA of trophoblast EPCR occurred when trophoblasts were challenged with tumor necrosis factor α, and it could be prevented by unfractionated heparin but not by low-molecular-weight heparin at therapeutic doses. In conclusion, there is a functional protein C pathway on human first-trimester trophoblasts which can be modulated by inflammation. This finding has implications for the pathogenesis and prevention of placenta-mediated obstetric complications.